Influence of biopesticides on growth (Colletotrichum capsici Sydow) Causes Antraknosa In Cayenne Pepper (Capsicum frutescens L.) - Sopialena Sopialena; Muhammad Alexander Mirza; Rani Soraya (Jurnal Agroekoteknologi Tropika Lembab, 2020)
ABSTRACK.This research aims to determine the influence of some plant extracts that are potentially as biopesticides on the growth and development of the mushroom Colletotrichum, Sydow and to know plant extracts that are able to suppress The growth and development of Colletotrichum's Capsisi Sydow. The study was conducted from March to April 2019, In the laboratory of Pest and disease grow Faculty of Agriculture, Mulawarman University. The method used is to use complete random draft (RAL) with 5 treatment that is potato dextrose so that, agar dextrose betel leaf, agar dextrose papaya leaves, so that the Dextrose lengbrush, agar dextrose garlic and repeated 10 times.The results showed the administration of betel leaf plant extracts, papaya leaves, galangal, and garlic has a prospect to be developed as a biopesticides to control mushrooms Colletotrichum capsici Sydow Cause of the antraknosa chili Peppers. The medium with betel leaf extract is the most effective extract to suppress the growth and development of Colletotrichum's capside of Sydow.